2015
DOI: 10.1016/j.molonc.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Serum N‐glycan analysis in breast cancer patients – Relation to tumour biology and clinical outcome

Abstract: Glycosylation and related processes play important roles in cancer development and progression, including metastasis. Several studies have shown that N-glycans have potential diagnostic value as cancer serum biomarkers. We have explored the significance of the abundance of particular serum N-glycan structures as important features of breast tumour biology by studying the serum glycome and tumour transcriptome (mRNA and miRNA) of 104 breast cancer patients. Integration of these types of molecular data allows us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 46 publications
0
31
1
Order By: Relevance
“…Haakensen et al . () observed that this glycan is correlated with decreased mitochondrial fatty acid beta oxidation. Decrease in this glycan in cancer indicates an increase in cell energy production.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Haakensen et al . () observed that this glycan is correlated with decreased mitochondrial fatty acid beta oxidation. Decrease in this glycan in cancer indicates an increase in cell energy production.…”
Section: Discussionmentioning
confidence: 91%
“…All glycans and derived glycan features were assigned in Saldova et al (2014). The major glycans in each peak, selected in Haakensen et al (2016), are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After separation by hydrophilic‐interaction chromatography (HILIC) or capillary electrophoresis, glycans are identified by mass spectrometry . Identification of individual oligosaccharides by their retention time in HILIC, enables very fast analysis of glycome, especially in biological fluids such as serum plasma, or urine . Profiling of both cell‐surface and intracellular glycans is more complicated and requires additional steps such as cell or tissue homogenization and fractionation .…”
Section: Analytical Approachesmentioning
confidence: 99%
“… underlined the necessity for a “multi‐omics” approach and data analysis in order to understand “the transition from healthy physiology to a disease state.” Haakensen et al. used this approach, and by studying the serum glycome and tumor transcriptome (mRNA and miRNA), they could demonstrate that the presence of circulating tumor cells is associated with certain glycome structures. Recent reviews present this approach, and its possible use for the optimization of different cancer therapies is widely discussed .…”
Section: Analytical Approachesmentioning
confidence: 99%